The Consequences of Stigma for Knowledge Production: Sheep Producers' Attitudes to Footrot Diagnostics and Control in Australia - Best, Nickala; Menéndez, Ramón; Rawlin, Grant; Suter, Robert; Rodoni, Brendan; Beddoe, Travis (Frontiers in Veterinary Science, 2020)
In Australia, there is documented confusion from producers around the clinical disease of footrot, and anecdotally, knowledge of what tools are available for the diagnosis and management of footrot. When discussing footrot with producers, the authors noted a hesitation to discuss, with denial often expressed. The disease can be debilitating, both on the sheep's welfare and the producer's well-being, as it is a very difficult disease to manage and eradicate. Gaining an understanding of producer perceptions of the disease may help ensure any future actions for management and control are in-line with those identified by producers. A combination of a web-based, and manually distributed surveys of 45 sheep producers was conducted. This included closed- and open-ended questions, multi check box, and Likert scales. Responses were quantified by descriptive statistics and a thematic analysis conducted of short answers. The results of this survey indicate satisfaction with footrot diagnostics is low, while satisfaction with control methods is high. There was also a poor general understanding of footrot as a disease, and a general distrust in peers when it comes to correct management of footrot. This research addresses a gap in the literature about how sociological conditions affect diagnosis and control of footrot disease. It provides three main recommendations—simplifying the diagnostic message, encouraging a culture of trust among sheep producers and increasing governmental support—as a way to tackle this problem.